Sibling stem cell donor experiences at a single institution - Wiener, Lori S. (2008)
Allogeneic bone marrow (BM) and cytokine mobilized peripheral blood stem cell (PBSC) transplantation can be curative for patients with malignant and nonmalignant hematologic diseases. Siblings are most often selected as a donor match; however, research on sibling donors is limited and has focused primarily on conventional BM donors. This exploratory study describes the experiences of PBSC sibling donors at a single institution. Through retrospective interviews, 14 sibling donors shared their perceived needs and concerns before and after their stem cell collection. Donors identified fears about the donation procedure, and expressed the need for more information about transplant outcome and complications. The inclusion of the sibling donors themselves, rather than the report of their parents or health-care providers and the qualitative nature of the structured design allowed sibling donors to describe their concerns and thoughts without being restrained by the beliefs of the participant’s parents, researcher or sibling’s medical team. Suggestions for visual educational tools, psychosocial interventions and future research are provided.